Teachers’ Perception of the Use of Video Conferencing Applications in Online Learning - Dewi Setyaningsih Mangkey; Muziatun Muziatun; Juhana Juhana (STAI Hubbulwathan Duri, 2023)
The objectives of this study were to analyze how the teachers’ perception of the use of video conferencing applications in online learning, to identify the challenges that the teachers had when implementing online learning utilizing video conferencing applications, and to find out the solutions to solve the obstacles faced by the teachers. The data of this study were collected through interviews and observation of six English teachers who teach students at elementary, junior high, and senior high levels in an informal English School in Gorontalo. The methodology employed in participant selection was the utilisation of purposive sampling. The data underwent analysis through the utilisation of a descriptive qualitative approach. The process consisted of three stages: data reduction, data display, and verification. The findings of this study indicate that all of the educators exhibited a favourable impression of their motivation in using video conferencing applications for teaching purposes, their competence in operating video conferencing applications, and their recognition of the benefits provided by such programmes. However, only a subset of the teachers had a strong understanding of the dynamics of their interactions with students and their students' levels of motivation. In addition to the aforementioned factors, educators faced various obstacles when utilising video conferencing platforms for online instruction. These challenges encompassed suboptimal internet connectivity, an unsupportive academic atmosphere for students, inadequate access to educational resources, limited opportunities for teacher-student engagement, and diminished student motivation. Ultimately, the educators proffered several strategies to circumvent the obstacles that had emerged, specifically by ensuring a reliable internet connection for the faculty, furnishing educational games, and upholding effective communication with the parents.